PENGARUH MOTIVASI TERHADAP KINERJA GURU PADA SD NEGERI SUKOHARJO BELITANG MULYA OKU TIMUR - Deni Kurniawan (Jurnal AKTUAL, 2021)
The results showed that the calculation results on the motivation variable where the value of t(count) is greater than t(table) that is 5.128 > 1.8595, then the motivation variable has an influence on the dependent variable, namely Teacher Performance. The value of R (square) or correlation coefficient which indicates the regression model formed by the interaction of variables. Motivation on teacher performance is 0.767 % which is interpreted that the independent variable used in this study shows an influence on the dependent variable of 76.7%, the remaining 23.3% is explained by other factors outside of the independent variables in this study. The t-test is shown from the value of the motivation variable at the value of t(count) 5.128 > t(table) 1.8595 which can be interpreted that the motivation variable has a very strong relationship to teacher performance. Keywords: Motivation, and Teacher Performance.